2018
DOI: 10.1103/physrevc.97.034329
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic description of triaxiality in Ru isotopes with covariant energy density functional theory

Abstract: Background: The triaxiality in nuclear low-lying states has attracted great interests for many years. Recently, the reduced transition probabilities for levels near the ground state in 110 Ru have been measured and provided strong evidences for a triaxial shape of this nucleus.Purpose: The aim of this work is to provide a microscopic study of low-lying states for the Ru isotopes with A ∼ 100 and to examine in detail the role of triaxiality, and the evolution of quadrupole shapes with the isospin and spin degre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 94 publications
1
6
0
Order By: Relevance
“…The predicted ground-state shape is consistent with the results of recent calculations with the relativistic Hartree-Bogoliubov formalism [16] using the density-dependent ME2 [56] and PC1 [57] parametrizations that predict minima in the PES of (β 2 , γ ) = (0.25, 15 • ) and (0.25, 17 • ), respectively. Nearly identical results [17] were found using the covariant density function theory with the PC-PK1 interaction [58] that yields a minimum at (0.25, 19 • ). The calculations using a self-consistent mean-field using the Gogny-D1M interaction predict that 102 Ru possesses some γ softness but with a prolate minimum at β 2 0.2 [15].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The predicted ground-state shape is consistent with the results of recent calculations with the relativistic Hartree-Bogoliubov formalism [16] using the density-dependent ME2 [56] and PC1 [57] parametrizations that predict minima in the PES of (β 2 , γ ) = (0.25, 15 • ) and (0.25, 17 • ), respectively. Nearly identical results [17] were found using the covariant density function theory with the PC-PK1 interaction [58] that yields a minimum at (0.25, 19 • ). The calculations using a self-consistent mean-field using the Gogny-D1M interaction predict that 102 Ru possesses some γ softness but with a prolate minimum at β 2 0.2 [15].…”
Section: Discussionsupporting
confidence: 67%
“…Other calculations using relativistic Hartree-Bogoliubov formalism with density-dependent zero-and finite-range nucleon-nucleon interactions found that shape coexistence did not manifest in any Ru isotope except 104 Ru [16]. Beyond-mean-field calculations employing the five-dimensional collective Hamiltonian with parameters determined by constrained self-consistent meanfield calculations based on the relativistic energy density functional PC-PK1 predicted that 100 Ru was nearly prolate, with a global minimum in the PES at (0.22, 4 • ), and 102 Ru had a triaxial minimum at γ = 19 • and was also predicted to be rather γ soft [17]. The PESs for 104,106 Ru were somewhat similar [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More localized studies are more numerous than the (rare) global surveys of triaxiality. Such studies generally concentrate on regions where the BSkG1 model also predicts triaxial ground state deformation, such as the Ge and Se isotopes in the A ∼ 70 region [109][110][111][112], the Kr, Sr, Zr, Mo and Ru isotopes in the A ∼ 100 region [113][114][115][116][117][118], and the neutron-rich rare-earths around A ∼ 190 [119][120][121].…”
Section: Deformationmentioning
confidence: 99%
“…The PNC scheme has also been adopted both in non-relativistic [49,50] and relativistic mean-field models [51] and the total-Routhian-surface method with the Woods-Saxon potential [52,53]. Most recently, the shell-model-like approach, originally referred to as PNC method, based on the cranking covariant density functional theory has been developed [54]. Note that the covariant density functional theory provides a consistent description of the nuclear properties, especially the spin-orbital splitting, the pseudo-spin symmetry [55,56,57,58,59,60,61,62,63,64] and the spin symmetry in the anti-nucleon spectrum [65,66], and is reliable for the description of nuclei far away from the β-stability line [67,68], etc.…”
Section: Introductionmentioning
confidence: 99%